PENGARUH STOSA ® TERHADAP NILAI ERITROSIT, LEUKOSIT, HEMOGLOBIN, PACKED CELLS VOLUME, SERTA TOTAL PROTEIN PLASMA KAMBING KACANG - , VINSA CANTYA PRAKASITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Livestock supplement is a feed additives which contains an element macro, micro, and nutrients required by livestock. STOSA is supplement that contains of vitamins, minerals, fatty acids, and amino acids that support the growth process and increase the endurance of livestock. The purpose of this study was to determine the effect of STOSA to erythrocytes, Hb, PCV, leukocyte & differential, and TPP. Sixteen goats were divided into four groups, each contains of four goats that raised since the age of four months. The treatment group was given STOSA with variation of 2 ml STOSA + 6 ml water (B), 4 ml STOSA + 4 ml water (C), and 8 ml STOSA (D), whereas control a given 8 ml of water to obtain the level of the same stress. The treatment is done once every day for 40 days. Blood sampling was performed on day 40th through the jugular vein and then performed blood tests and analyzed . The result showed that value of erythrocytes of group A 8,96 ± 0,29, B 8,75 ± 0,34, C 9,18 ± 1,61, D 9,36 ± 0,29